A novel phylogeny and morphological reconstruction of the PIN genes and first phylogeny of the ACC-oxidases (ACOs) - Clouse, Ronald M.; Carraro, Nicola (Frontiers in Plant Science, 2014)
The PIN and ACO gene families present interesting questions about the evolution of plant physiology, including testing hypotheses about the ecological drivers of their diversification and whether unrelated genes have been recruited for similar functions. The PIN-formed proteins contribute to the polar transport of auxin, a hormone which regulates plant growth and development. PIN loci are categorized into groups according to their protein length and structure, as well as subcellular localization. An interesting question with PIN genes is the nature of the ancestral form and location. ACOs are members of a superfamily of oxygenases and oxidases that catalyze the last step of ethylene synthesis, which regulates many aspects of the plant life cycle. We used publicly available PIN and ACO sequences to conduct phylogenetic analyses. Third codon positions of these genes in monocots have a high GC content, which could be historical but is more likely due to a mutational bias. Thus we developed methods to extract phylogenetic information from nucleotide sequences while avoiding this convergent feature. One method consisted in using only A-T transformations, and another used only the first and second codon positions for serine, which can only take A or T and G or C, respectively. We also conducted tree-searches for both gene families using unaligned amino acid sequences and dynamic homology. PIN genes appear to have diversified earlier than ACOs, with monocot and dicot copies more mixed in the phylogeny. However, gymnosperm PINs appear to be derived and not closely related to those from primitive plants. We find strong support for a long PIN gene ancestor with short forms subsequently evolving one or more times. ACO genes appear to have diversified mostly since the dicot-monocot split, as most genes cluster into a small number of monocot and dicot clades when the tree is rooted by genes from mosses. Gymnosperm ACOs were recovered as closely related and derived.